2018
DOI: 10.1002/jlb.3a1017-411rr
|View full text |Cite
|
Sign up to set email alerts
|

ITGB4is essential for containing HDM-induced airway inflammation and airway hyperresponsiveness

Abstract: Airway epithelial cells play a significant role in the pathogenesis of asthma. Although the structural and functional defects of airway epithelial cells have been postulated to increase asthma susceptibility and exacerbate asthma severity, the mechanism and implication of these defects remain uncertain. Integrin β4 (ITGB4) is a structural adhesion molecule that is downregulated in the airway epithelium of asthma patients. In this study, we demonstrated that ITGB4 deficiency leads to severe allergy-induced airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…RT‐PCR was conducted according to the PrimeScript™ RT Master Mix Kit (Takara, Japan). Quantitative PCR (qPCR) was performed on a CFX96 Touch™ Deep Well Real‐Time PCR Detection System (Bio‐rad, USA) by the use of TB Green ® Premix Ex Taq (Takara, Japan) with thermal cycling conditions 24 . Primer sequences were described in Supplementary Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…RT‐PCR was conducted according to the PrimeScript™ RT Master Mix Kit (Takara, Japan). Quantitative PCR (qPCR) was performed on a CFX96 Touch™ Deep Well Real‐Time PCR Detection System (Bio‐rad, USA) by the use of TB Green ® Premix Ex Taq (Takara, Japan) with thermal cycling conditions 24 . Primer sequences were described in Supplementary Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid lethal effect of ITGB4 null mice, we constructed a conditional ITGB4 deficiency model: CCSP–rtTA tg/− /TetO‐Cre tg/− /ITGB4 fl/fl . In the model, ITGB4 was deleted only in the airway epithelial cells . Then, SA‐β‐gal was used to detect the senescence in airway epithelial cells .…”
Section: Resultsmentioning
confidence: 99%
“…Ozone‐challenged mice were stressed with ozone (2.0 ppm, 30 min) for 4 days and killed 12 h after the last exposure, whereas the control mice were treated with fresh air . The conditional ITGB4 knockout mice were constructed according to our previous procedures .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu and co-workers revealed that ITGB4 is involved in airway hyper-responsiveness and lung in ammation in allergic asthma. ITGB4-de cient mice displayed increased in ltration of lymphocyte, neutrophil, and eosinophil as well as expression of IL-4, IL-13, and IL-13A in lung tissue [89]. Tang et al showed that ITGB4-de ciency causes spontaneous exaggerated lung in ammation in early life [90].…”
Section: Gene Ontology Analysis Of Allergy Related Proteins Associatementioning
confidence: 99%